The effect of attacking tactical skill exercises in the skills of dribbling and shooting for youth football players - Kadhim Ali, Naji; Saad Abdul Hameed, Ali; Saad Ibrahim, Samer (International Journal of Psychosocial Rehabilitation, 2020)
The exercises skills tactically had a role positive in the development of the level of performance skills, basic and implementation represented the evolution of the time of this performance and accuracy of through the link between the speed and accuracy, clear when the application of performance tests of the three 0 The exercise used was a quality, good, and oriented and progressive, which brought about the change. Effective and efficient in the implementation of the performance of technical skills essential that reflected on the results of the group's experimental in tests posteriori. The mastery of skills reel foot on according to a plan thought provides an opportunity for the team beneficiary of them because the perfectly skilled are essential when implementing the performance of the tactical year, as the repetition of regular helps to improve and develop the application of skills for the implementation of these tests, the basic 0 of the use methods, different exercises, skills, tactical attacking, and not relying on style one. The importance of mastering the skills is the vehicle as the most connected inhabitants and play during the games from the born player and the team. Attention must be paid to the skills most related to the requirements of play to achieve the skill requirements for the planned performance to achieve positive results. We emphasize training offensive tactical skills throughout the general and special preparation period and for competitions at different rates.